The Direct Cost of Treatment of Traumatic Brain Injury in a Sub-Saharan African Country (Benin)..... - HODE, LUPHIN; MADOUGOU, SOUMAÏLA; FATIGBA, O.H; HOUNNOU, PHILEAS; EBASSA, KARL; HANS MOEVI, ARISTOTE; ASSOUTO, ASSOGBA PAMPHILE (My University, 2016)
OBJECTIVES: This is the first socioeconomic study on traumatic brain injury (TBI) undertaken to determine the sociodemographic factors implicated in the occurrence of TBI and to assess the value of the direct cost of the management of TBI at the initial phase in the Hubert Koutoukou Maga National Teaching Hospital of Cotonou. - METHODS: This was a prospective study with descriptive and analytic aim that took place from January 1 to July 31, 2014. An individual approach of each patient’s expenditure was undertaken via the use of a questionnaire on which all expenses were identified systematically. The dependent variable was the global direct cost of care. The independent variables were the type of accident, severity of the TBI, the structures of care, the stay in the resuscitation unit, the duration of hospitalization. - RESULTS: There were 297 patients with TBI: 258 men (86.9%) and 39 women (13.1%), with a sex ratio of 6.61. The average age of patients was 34.3 12.39 years. The average direct cost of care for TBI was V285.67 310.15. The average cost for severe TBI was V522.08 439.91 versus V188.19 164.83 for mild TBI (odds ratio 5.52; standard deviation: 0.0527e0.6222). The average cost was increased significantly more when the patients went through a peripheral hospital (odds ratio 3.65; standard deviation: 1.819e7.3245). - CONCLUSIONS: The organization of Benin’s health system did not allow for the optimum management of TBI. It seems imperative to develop an insurance system that will
Keywords: Africa; - Benin; - Cost; - Traumatic brain injury